RANCANG BANGUN DAN PERAN BENTENG SUMENEP - Novida Abbas (Berkala Arkeologi, 2006)
From several sources obtained regarding the existence of the Dutch fort in Sumenep, it appears that there were various events that occurred during the usage of the fort. In addition, there are several conflicting matters which still require further explanation. Various sources say that at first the Sumenep fortress had both military and civilian functions, which is evident from the mention of the fort as the residence of the Dutch trade representatives, although in the end the fort only functioned militarily, namely by adding troops who protected the fort and the appointment of a lieutenant as commander. There was also resistance to the British, which probably involved the fort as a means of defense.